Recent advances in functional materials and devices for Zn-Ion hybrid supercapacitors - Weijia Fan; Faxing Wang; Xiaosong Xiong; Bingyan Song; Tao Wang; Xinbing Cheng; Zhi Zhu; Jiarui He; Yankai Liu; Yuping Wu (NPG Asia Materials)
Abstract Zinc-ion hybrid supercapacitors (ZHSCs) are attracting significant attention due to their high energies/power densities, safety, and low cost. In this review, recent advances in the development of ZHSCs are summarized. Particular emphasis is placed on state-of-the-art cathodes (including carbon, metal oxides, MXenes, and redox-active polymers), anodes (including Zn-based composites and Zn-free materials) and electrolytes for ZHSCs. Furthermore, the latest research on functional ZHSC devices with miniaturized ZHSCs, fiber-shaped ZHSCs, self-chargeable ZHSCs and self-healing devices is reported. Finally, further developments with ZHSCs are envisaged for future research in this thriving field.